STRATEGIES FOR REPRESENTING SOCIAL ACTORS: A CASE STUDY - Hoa, Nguyen (VNU Journal of Foreign Studies, 2021)
The study explored the strategies used for representing the two social actors, Donald Trump and Hillary Clinton as a case-study. Data was the transcript of the speech delivered at the 2016 Democratic National Convention (DNC) by President Obama. Grounded in the view that an actor is defined in terms of who he is and what he does, the study adopted a combined approach drawn on van Leeuwen’s social actor representation framework (SAR) and Halliday’s transitivity analysis. Findings reveal the speaker deployed selected strategies to support, to identify with Clinton, and to other Trump at the same time. The use of van Dijk’s ideological square showed how the Us vs. Them characterization functioned as a strategy to further legitimation or de-legitimation of social actors. The study suggests that representations are potentially biased. However, it implicitly recognizes a more powerful role of non-discursive social practices. Implications and suggestions for future research are offered.